2017
DOI: 10.1103/physrevb.95.035140
|View full text |Cite
|
Sign up to set email alerts
|

Translational symmetry breaking and the disintegration of the Hofstadter butterfly

Abstract: We study the effect of interactions on the Hofstadter butterfly of the honeycomb lattice. We show that the interactions induce charge ordering that breaks the translational and rotational symmetries of the system. These phase transitions are prolific and occur at many values of the flux and particle density. The breaking of the translational symmetry introduces a new length scale in the problem and this affects the energy band diagram resulting in the disintegration of the fractal structure in the energy flux … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Introducing electron-electron interactions is known to produce a rich set of symmetry-broken phases in graphene for weak fields. [34][35][36][37] There have been a few investigations into interaction effects in the Hofstadter regime, [38][39][40][41][42] but a full picture remains to be developed. GM thanks David Mross for a vauable discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Introducing electron-electron interactions is known to produce a rich set of symmetry-broken phases in graphene for weak fields. [34][35][36][37] There have been a few investigations into interaction effects in the Hofstadter regime, [38][39][40][41][42] but a full picture remains to be developed. GM thanks David Mross for a vauable discussion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand the on-site Hubbard interaction drives the system towards an anti-ferromagnetic configuration which is also an insulating state [15]. Recently it is shown that interaction also induces charged ordering in the Hofstadter butterfly [16,17], however for Bose-Hubbard model in the presence of magnetic field such charge density order is absent [18,19]. On varying the on-site Hubbard interaction in presence of disorder, the system therefore undergoes a transition from disorder driven insulator to correlation driven insulator.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies related to the interaction driven quantum Hall and quantum spin Hall phases [24][25][26][27][28][29] . In addition, the effect of interactions in the Hofstadter regime has also been studied extensively, showing spontaneous breaking of translational and rotational symmetries of the system prompting topological transitions [30][31][32][33][34][35][36] . Similarly, interplay of interactions and SOC on the lattice system has also been widely explored and several exotic phases such as Mott topological insulators and magnetic Chern insulators have been investigated as an outcome 16,24,28,[37][38][39][40][41][42][43] .…”
Section: Introductionmentioning
confidence: 99%